Three Disentanglements for the Exhausted Geographies - Almac, Bihter; Altunok, Nilsu; Atacan, Oya Yesim Armagan; Giriftinoglu, Nazli (TAYLOR & FRANCIS INC, 2025)
Eco-social imaginaries-the tales and spectacle of our interpretation in dealing with the associated ecology of our built and social worlds-are always at work in our everyday lives. Extraction is intricately inherent as an aspect of this and shapes our myths, childhood memories, the color of the lands around us, where we dance, and even where seagulls gather. This article discusses attempts of disentanglement in three zones of sacrifice using feminist research methods in design in the form of architectural essay films. We claim that essayistic filmmaking is an approach to eco-social imaginaries that could enable graduate research to unbound itself from closeted methodologies that overlook situated knowledge, affects, matters of concern and more than human worlding. We discuss this within the posthumanist feminist approach and feminist pedagogies.
Keywords: exhausted geographies; architectural essay film; feminist research methods; feminist pedagogy; creative research; Architecture